The adaptive immune system in early life: The shift makes it count - Pieren, Daan K. J.; Boer, Mardi C.; de Wit, Jelle (Frontiers in Immunology, 2022)
Respiratory infectious diseases encountered early in life may result in life-threatening disease in neonates, which is primarily explained by the relatively naive neonatal immune system. Vaccinations have greatly reduced childhood mortality, although repeated vaccinations are required to reach protective immunity in infants and not all vaccinations are effective at young age. Moreover, protective adaptive immunity elicited by vaccination wanes more rapidly at young age compared to adulthood. The infant adaptive immune system has previously been considered immature but this paradigm has changed during the past years. Recent evidence shows that the early life adaptive immune system is equipped with a strong innate-like effector function to eliminate acute pathogenic threats. These strong innate-like effector capacities are in turn kept in check by a tolerogenic counterpart of the adaptive system that may have evolved to maintain balance and to reduce collateral damage. In this review, we provide insight into these aspects of the early life’s adaptive immune system by addressing recent literature. Moreover, we speculate that this shift from innate-like and tolerogenic adaptive immune features towards formation of immune memory may underlie different efficacy of infant vaccination in these different phases of immune development. Therefore, presence of innate-like and tolerogenic features of the adaptive immune system may be used as a biomarker to improve vaccination strategies against respiratory and other infections in early life.